2010
DOI: 10.1017/s0007114510000759
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to zinc deficiency in fetal and postnatal life determines nitric oxide system activity and arterial blood pressure levels in adult rats

Abstract: We had previously shown that prenatal exposure to Zn-deficient diets induces an increase in blood pressure and impairs renal function in adult rats. The aim of the present study was to investigate if moderate Zn restriction during early growth periods, fetal life and lactation would induce impairment in the vascular and renal NO system and alterations in plasma lipid profile. We also investigated if these effects persisted into adult life, even when a Zn-replete diet was provided after weaning. Pregnant rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…However, this alteration could not be prevented by an adequate zinc diet after weaning. This degree of blood pressure elevation dramatically increases the risk of cardiovascular events (40,41,42,44,48). Moreover, in the present study, we demonstrated, for the first time, that fetal and postnatal zinc restriction does not modify blood pressure levels in females.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, this alteration could not be prevented by an adequate zinc diet after weaning. This degree of blood pressure elevation dramatically increases the risk of cardiovascular events (40,41,42,44,48). Moreover, in the present study, we demonstrated, for the first time, that fetal and postnatal zinc restriction does not modify blood pressure levels in females.…”
Section: Discussionsupporting
confidence: 57%
“…Dietary zinc restriction during fetal life and lactation induces an increase in arterial blood pressure and impairs renal function in adult male rats (40,42,43).…”
mentioning
confidence: 99%
“…Our study also showed that increased serum nitric oxide levels were also associated with low scores for signs and symptoms of CMS. Recently, it has been demonstrated that nitric oxide and Zn are endogenous signaling molecules acting in response to environmental stress [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…As observed in other cell types, zinc deficiency decreased activities and amounts of oxidant defense system components, increased oxidative damage to lipids, and increased apoptosis (Tomat et al, 2008). Moderate zinc deficiency during pregnancy and lactation also led to decreased nitric oxide synthase (NOS) activity in the vasculature of aortic artery and resistance arterioles, and in kidney nephrons that persisted into adulthood despite zinc repletion at weaning (Tomat et al, 2010). The expression of endothelial NOS (eNOS) in the thoracic aorta was lower in the low zinc groups compared to controls (Tomat et al, 2010).…”
Section: Long-term Effects Of Gestational Zinc Deficiencymentioning
confidence: 97%
“…Moderate zinc deficiency during pregnancy and lactation also led to decreased nitric oxide synthase (NOS) activity in the vasculature of aortic artery and resistance arterioles, and in kidney nephrons that persisted into adulthood despite zinc repletion at weaning (Tomat et al, 2010). The expression of endothelial NOS (eNOS) in the thoracic aorta was lower in the low zinc groups compared to controls (Tomat et al, 2010). Thus, maternal and lactational zinc deficiency leads to lower nitric oxide production and renal dysfunction in the offspring that persist into adulthood leading to increased risk for cardiovascular complications such as hypertension.…”
Section: Long-term Effects Of Gestational Zinc Deficiencymentioning
confidence: 99%